Identification of the Combination of Factors Decreasing Stunting in Indonesia, using the QCA method: Identifikasi Kombinasi Faktor Penurunan Stunting di Indonesia, menggunkan metode QCA - Mega, Endang Mega Utami; Deddy Yuliawan; Vitriyani Tri Purwaningsih (Goodwood Publishing, 2025)
Stunting remains a critical challenge in improving human capital development in Indonesia. Despite numerous government intervention programs, their effectiveness in reducing stunting prevalence has not been comprehensively evaluated. This study aims to assess the effectiveness of government interventions in addressing stunting using the multi-value Qualitative Comparative Analysis (mvQCA) method, based on data from 34 provinces in Indonesia. The variables analyzed include complete basic immunization coverage, exclusive breastfeeding, National Health Insurance (JKN) ownership, access to proper sanitation, active community health posts (Posyandu), average years of schooling for women, and poverty levels. The results reveal that no single factor is consistently sufficient to reduce stunting rates. Instead, combinations of these factors form effective configurations in lowering stunting prevalence. These findings highlight the importance of adopting a holistic and contextual policy approach in tackling stunting across different regions. This study provides valuable policy implications for designing more targeted and effective interventions to combat stunting in Indonesia. Keywords: stunting, government intervention, mvQCA, health policy, sanitation, exclusive breastfeeding, immunization, health insurance.